Face - saving strategies in teachers' Oral feedback in English classrooms - A Vietnamese - American cross-cultural study : M.A. Thesis Linguistics: 60 22 15 - Ngô, Thị Phương Lê (2017)
To investigate the face-saving strategies used by American and Vietnamese teachers when giving oral feedback to students in English classrooms. To clarify major similarities and differences between American and Vietnamese teachers when giving different types of feedback. To provide implications in English Language Teaching and contribute to increasing cross-cultural awareness among English language teachers and learners.